SIMULATION OF STRATIFICATION BEHAVIOR OF TWO IMMISCIBLE FLUIDS USING FINITE VOLUME PARTICLE (FVP) METHOD - Faris Kamal Islahi; Nur Asiah Aprianti; Asril Pramutadi Andi Mustari; Koji Morita (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2023)
In this modern era, the need for energy is increasing, and the environmental issues caused by the energy industry are also increasing. Therefore, one of the long-term alternative energy sources is nuclear energy. However, as is well known, there have been many nuclear reactor accidents, such as the Chernobyl, Three Miles Island, and Fukushima reactors. In those cases, there was an accident in the core reactor, especially the melting of the reactor core. One phenomenon is the stratification of the molten metal component of the melted reactor core. Using simulation, this study will discuss the stratification behavior of two immiscible and incompressible fluids. The particle-based simulation method has advantages over the mesh method in simulating free surface conditions and has a lighter computational load. The particle method used in this simulation is the Finite Volume Particle (FVP) method, derived based on the finite volume method by assuming each particle occupies a certain volume. The simulation of the stratification behavior is carried out using three types of fluids, water, cooking oil, and lubricating oil, which are combined into three variations. The stratification simulation results will be compared with the experimental results obtained from the reference. From the simulation results obtained, there is a pattern similar to the experimental results. Simulation data is also processed to obtain the penetration ratio between fluids in each variation and the length of water penetration through cooking and lubricating oil. The results show that the magnitude of the difference in fluid density and viscosity affects the stratification process.